Accentual phrases in Tagalog intonation and their loose relation to word prosody - Farinella, Alessa; Jun, Sun-Ah (Proceedings of the Linguistic Society of America, 2025)
In this paper, we present a preliminary analysis of Tagalog intonational phonology. We argue for three levels of prosodic phrasing above the prosodic word: an Accentual Phrase (AP), an Intermediate Phrase (iP) and an Intonational Phrase (IP). Each of these phrases are defined by edge tones, which contributes to the regular tonal melody of Tagalog utterances. We argue that Tagalog is typologically unusual in that some tones display variability in terms of their alignment: sometimes these tones target prominent syllables, while other times they appear to ignore them and target phrase edges. In particular, the left edge tone of an iP-medial AP is some- times aligned to an (unstressed) AP-initial syllable, and other times is aligned to the stressed syllable of an AP-initial word. This finding suggests that Tagalog repre- sents a new type of language, one with variable tonal alignment, which is not easily accounted for in the Autosegmental-Metrical theory of intonational phonology.